Breast-feeding and postpartum maternal weight trajectories. Issue 8 (15th October 2015) - Mullaney, Laura; O'Higgins, Amy C; Cawley, Shona; Kennedy, Rachel; McCartney, Daniel; Turner, Michael J
Abstract: Objective: We examined whether breast-feeding, and in particular exclusive breast-feeding, was associated with maternal weight and body composition changes at 4 months postpartum independently of other maternal variables. Design: Prospective longitudinal study. Women were recruited in the first trimester after an ultrasound examination confirmed an ongoing singleton pregnancy. Weight and body composition were measured using advanced bio-electrical impedance analysis at the first antenatal visit and 4 months postpartum. Detailed questionnaires were completed on breast-feeding, socio-economic status, diet and exercise in addition to routine clinical and sociodemographic details. Setting: Large Irish university maternity hospital. Subjects: Women who delivered a baby weighing ≥500 g between November 2012 and March 2014. Results: At the postpartum visit, the mean weight was 70·9 (sd 14·2) kg ( n 470) and the mean BMI was 25·9 (sd 5·0) kg/m 2 . 'Any breast-feeding' was reported by 65·1 % of women ( n 306). Irish nativity (OR=0·085, P <0·001), current smoking (OR=0·385, P =0·01), relative income poverty (OR=0·421, P =0·04) and deprivation (OR=0·458, P =0·02) were negatively associated with exclusive breast-feeding. At 4 months postpartum there was no difference in maternal weight change between women who exclusively breast-fed and those who formula-fed (+2·0 v . +1·1 kg, P =0·13). Women who exclusively breast-fed had a greater increase in percentage body fat at 4 months postpartum compared with women who formula-fed (+1·0 v . −0·03 %, P =0·02), even though their dietary quality was better. Exclusive breast-feeding was not associated with postpartum maternal weight or body fat percentage change after adjusting for other maternal variables. Conclusions: There are many reasons why breast-feeding should be strongly promoted but we found no evidence to support postpartum weight management as an advantage of breast-feeding.